Nghiên cứu tổng hợp chất hoạt động bề mặt lignosunfonat từ dịch thải của công nghiệp sản xuất bột giấy, ứng dụng trong gia công thuốc bảo vệ thực vật - Hoằng, Đào Văn (Vietnam Journal of Chemistry, 2014)
Lignosulfonates have been used as surfactants in many field of industry. Based on the survey of several main lignosulfonate synthesis methods, the methylsulfonation of lignin, obtained from black liquor, a waste water from kraft pulping proces was investigated. The mixture of formalin and sodium sulfite was selected and used as methylsulfonation agent. The suitable conditions for this reaction were examined and optimized (molar ratio of reactants, time of reaction, amount of sulfonation agent...). The products were identified and characterized by Infrared Spectroscopy and sulfonation degree measuring (through sulphur element determination in the product). The products are successfully used as multifunctional surfactants in the formulation of two commercial fungicides: Copper oxychloride 30WP and Sulphur 80 WDG.